Acolhimento socioemocional de professoras e professores na rede municipal de ensino de Castro Alves-BA: possibilidades e estrat?gias para minimizar os efeitos causados pelo per?odo pand?mico - Bastos, Verena Rebou?as de Santana (2024)
This work seeks to analyze the impacts caused by the Covid 19 pandemic on the daily lives of schools in the municipal education network of Castro Alves ? Bahia, with regard to the fulfillment of the academic years of 2020, 2021 and 2022, which had their face-to-face classes suspended due to the need for social distancing. It was observed that, given the public emergency and the changes that were imposed by the pandemic period, there was a chain increase in sick people who are part of the school community, such as teachers and students. Problems were identified during the pandemic, or existing ones, but exacerbated during the period, such as anxiety, stress, panic syndrome, depression, student self-injury, among others. To this end, the work was developed to address the following problematizing question: How do schools in the Final Years of Elementary Education in the municipal education network of Castro Alves, Bahia, promote socio-emotional support for teachers in the context of returning to face-to-face classes? In this sense, the general objective is to analyze the process of socio-emotional reception of teachers when returning to face-to-face classes after the remote period in the municipal education network of Castro Alves-BA. And also as specific objectives: to develop a Pedagogical Guide that can support welcoming actions in the school environment; debate with the school public about the prospects for improving the school environment, through discussions linked to the theme of socio-emotional reception; promote meetings with teachers for listening moments at school with the aim of developing a diagnosis and identifying symptoms that lead to illness; contribute to the development of practices, projects and programs in schools, which help to minimize the socio-emotional impacts of returning to face-to-face classes. This construction took place through stages carried out, based on workshops with studies, analyzes of theorists and situations experienced in the context of a School for the Final Years of Elementary Education in the municipality of Castro Alves, Bahia, in addition to analysis of current legislation, such as the Curricular Reference of the Municipality of Castro Alves, Pedagogical Political Project for schools, Protocol for resuming face-to-face classes. having as an educational product a Pedagogical Guide with strategies to be used in all seven schools in the Final Years of Elementary Education in that municipality. This will mainly be done through continued training on the topic addressed and constant listening to the school community.During the research, the reports and listening were systematized and presented in this dissertation. In order to meet the desired objectives, I used research techniques, such as the diagnostic questionnaire, preparation of a symptom identification report with teachers, holding seminars and workshops, aiming to enhance the collection of information that supported the preparation of the Pedagogical Guide.